Atención al cliente en la ferretería william lui de la parroquia san juan - Mogro Mariscal, Johanna Carolina (2022)
The hardware store "William Lui", based on the various problems it presents due to low profitability in its sales, has sought the alternative to improve customer service within the family business to increase the attraction and loyalty of customers in order to improve its sales. The problematic situation is based on a high percentage of complaints and claims, so it is imperative to solve the problems presented by customers who are not well served by the employees of the microenterprise. The results of the analysis determined the current situation of the company. It was found that customers are not satisfied with the service offered and their complaints and requirements are not immediately attended to. It was also determined that the company's employees are not friendly when attending to customers and are not sufficiently trained to offer immediate solutions.